2014
DOI: 10.1071/he13095
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and beliefs about lung cancer in three culturally and linguistically diverse communities living in Australia: a qualitative study

Abstract: Limited awareness of the signs and symptoms of lung cancer, combined with cultural perceptions about cancer, impacted on attitudes towards help-seeking behaviour in these three CALD communities. So what? The prevalence of smoking among Chinese men, Vietnamese men and Arabic-speaking communities in NSW puts them at increased risk of lung cancer. Health promotion initiatives for lung cancer should be tailored for CALD communities and could focus on increasing knowledge of key symptoms, awareness that ex-smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…At present, there is limited literature on nutritional outcomes for cancer patients from CALD backgrounds. Various studies have proposed that patients from CALD backgrounds have a different attitude and understanding of health when compared with their non‐CALD counterparts . This difference might lead to poorer compliance with the dietitian recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, there is limited literature on nutritional outcomes for cancer patients from CALD backgrounds. Various studies have proposed that patients from CALD backgrounds have a different attitude and understanding of health when compared with their non‐CALD counterparts . This difference might lead to poorer compliance with the dietitian recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the Chinese, Vietnamese and Arabic‐speaking communities in Sydney, Australia, had limited awareness of signs and symptoms of lung cancer. Their cultural perceptions about cancer and level of trust in general practitioners had a significant impact on their willingness in seeking medical advice …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Australia is a multicultural nation yet Indigenous Australians and other minority groups face prejudice and ongoing challenges in their lives. 48 Strategies to deliver health service commensurate with societal changes and which consider cultural differences must continue to be explored so outcomes can improve.…”
Section: Culture and Health Decisionsmentioning
confidence: 99%